REFERENCE VALUES FOR LEISHMANIA INFANTUM PARASITEMIA IN DIFFERENT CLINICAL PRESENTATIONS: QUANTITATIVE POLYMERASE CHAIN REACTION FOR THERAPEUTIC MONITORING AND PATIENT FOLLOW-UP - MARY, CHARLES; FARAUT, FRANCOISE; DROGOUL, MARIE-PIERRE; XERIDAT, BERNARD; SCHLEINITZ, NICOLAS; CUISENIER, BERNADETTE; DUMON, HENRI (The American journal of tropical medicine and hygiene, 2006)
Quantification of Leishmania infantum DNA in blood samples by an ultrasensitive quantitative polymerase chain reaction (QPCR) detected parasitemias in different clinical presentations. We observed a large range of parasitemias, more than 9 log values, and could determine the threshold between asymptomatic carriage and disease in the Mediterranean area (approximately one parasite/mL of blood. Based on kinetoplast DNA amplification, this assay had a sensitivity of 0.001 parasite DNA equivalents/mL and detected asymptomatic carriage of Leishmania . It detected parasite DNA in 58% of healthy subjects, while an immunoblot detected specific antibodies in only 16%. For initial diagnosis of disease, this quantitative PCR with blood samples constitutes a non-invasive alternative to bone marrow aspiration. Its main applications are monitoring of drug therapy and follow-up of immunodeficient patients for biologic confirmation of relapses.